Time-course analysis and transcriptomic identification of key response strategies of Nelumbo nucifera to complete submergence. Issue 1 (11th February 2022) - Deng, Xianbao; Yang, Dong; Sun, Heng; Liu, Juan; Song, Heyun; Xiong, Yaqian; Wang, Yunmeng; Ma, Junyu; Zhang, Minghua; Li, Jing; Liu, Yanling; Yang, Mei
Abstract: Water submergence is an environmental stress with detrimental effects on plant growth and survival. As a wetland plant species, lotus ( Nelumbo nucifera ) is widely cultivated in flood-prone lowlands throughout Asian countries, but little is known about its endurance and acclimation mechanisms to complete submergence. Here, we performed a time-course submergence experiment and an RNA-sequencing transcriptome analysis of the two lotus varieties "Qiuxing" and "China Antique". Both varieties showed low submergence tolerance, with a median lethal time of approximately 10 days. Differentially expressed gene (DEG) analysis and weighted gene co-expression network analysis (WGCNA) identified a number of key genes putatively involved in lotus submergence responses. Lotus plants under complete submergence developed thinned leaves and elongated petioles containing a high density of aerenchyma. All four lotus submergence-responsive ERF-VII genes and gene sets corresponding to the low oxygen "escape" strategy (LOES) were elevated. In addition, a number of lotus innate immunity genes were rapidly induced by submergence, probably to confer resistance to possible pathogen infections. Our data also reveal the probable involvement of jasmonic acid in the modulation of lotus submergence responses, although to a lesser extent than the gaseous hormone ethylene. These results suggest that lotus plants primarily use the LOES strategy to cope with complex submergence-induced stresses, and they will be valuable for understanding the molecular basis underlying plant submergence acclimation.